Institutional Logic Conflict in Performance-Based Budget Reform: A Qualitative Study of Private University Governance - Indudewi, Dian; Nafasati, Febrina; Wardoyo, Paulus (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
This study is motivated by the increasing demand for financial accountability and discipline in private non-profit universities that primarily rely on student-derived funding, particularly amid leadership transitions and budgeting reforms. The research aims to examine the practical challenges of implementing performance-based budgeting within the management control system at PTS X in Semarang. A qualitative single-case study design was employed. Data were collected through in-depth interviews with 11 key managerial actors, including vice rectors, deans, bureau heads, and work unit leaders directly involved in budget allocation. The data were analyzed using NVIVO to identify key managerial issues and coordination challenges during the budgeting process. The findings reveal that the adoption of the money follows program approach and the use of Key Performance Indicators (KPIs) enhanced budget structure and accountability. However, its effectiveness was constrained by an uneven understanding of KPIs at the operational level and frequent budget adjustments. The study concludes that strengthening internal communication, deepening KPI internalization, and ensuring policy consistency are essential to optimizing the full management control system cycle.